2016
DOI: 10.1177/1535370216648804
|View full text |Cite
|
Sign up to set email alerts
|

Original Research: Establishment of an early embolus-related cerebral injury model after cardiopulmonary bypass in miniature pigs

Abstract: Embolus-related cerebral injury is still a serious adverse event after cardiopulmonary bypass (CPB). But there is no stable animal model for basic and clinical research purposes. We chose miniature pig to establish a stable animal model of embolus-related cerebral injury after CPB and verified the validity of results by correlating the histopathological findings with those of diffusionweighted magnetic resonance imaging (DW-MRI). Based on different treatment regimens, 24 male miniature pigs were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The mechanism of brain injury after CPB is complex with major causes that include cerebral emboli (gas, liquid, or solid), cerebral ischaemic injury (e.g., vascular embolism, hypoperfusion, and hypoxia), and inflammatory responses. 3 , 21 During CPB, stimulation by surgical trauma, blood contact with foreign bodies, body endotoxins, and a low temperature activate non-infectious systemic inflammatory response syndromes. 4 Therefore, a large number of inflammatory cytokines enter the brain, leading to brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of brain injury after CPB is complex with major causes that include cerebral emboli (gas, liquid, or solid), cerebral ischaemic injury (e.g., vascular embolism, hypoperfusion, and hypoxia), and inflammatory responses. 3 , 21 During CPB, stimulation by surgical trauma, blood contact with foreign bodies, body endotoxins, and a low temperature activate non-infectious systemic inflammatory response syndromes. 4 Therefore, a large number of inflammatory cytokines enter the brain, leading to brain damage.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Several studies have shown that CPB-mediated brain injury is associated with embolism, hypoperfusion, arrhythmias, rapid rewarming, and inflammation. 3 , 4 , 7 Moreover, a substantial amount of research has been conducted into brain injury associated with CPB in relation to different cell factors and signal pathways. 5 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence of complications related to the nervous system has remained consistent. The mechanism of brain injury after CPB is complex, with major causes including cerebral emboli (gas, liquid, or solid), cerebral ischaemic injury (such as vascular embolism, hypo perfusion, and hypoxia), and inflammatory responses [19,20]. During CPB, stimulation by surgical trauma, blood contact with foreign bodies, body endotoxins, and a low temperature activate non-infectious systemic inflammatory response syndromes [21].…”
Section: Discussionmentioning
confidence: 99%